Why individual investors invest in ESG mutual funds : Pecuniary and non-pecuniary factors for investment behavior - Niemelä, Eeli (My University, 2026)
Environmentalism and responsibility have been a global trend for some time now. This same trend has also become part of the investment market. Therefore, this thesis examines how pecuniary and non-pecuniary factors influence retail investors’ investment decisions when choosing ESG mutual funds. Based on previous studies, this research concluded that the performance of ESG funds has generally been either worse than or on par with conventional funds, except during times of crisis. At the same time, investors have viewed ESG funds as safer and less volatile investments compared to their benchmark funds. In addition, non-pecuniary factors—the strongest evidence for which came from warm glow, incidental guilt, social preference, and confirmation bias—have a positive impact on individual investors’ investment decisions.

Ekologisuus ja vastuullisuus ovat olleet maailmanlaajuinen trendi jo jonkin aikaa, ja sama kehitys on vakiintunut myös sijoitusmarkkinoille. Tässä tutkielmassa tarkastellaan, miten taloudelliset ja ei-taloudelliset tekijät vaikuttavat yksityissijoittajien sijoituspäätöksiin heidän valitessaan ESG-sijoitusrahastoja. Aikaisempien tutkimusten perusteella, ESG-rahastojen tuotto on yleensä ollut huonompi, tai samaa tasoa perinteisten rahastojen kanssa kriisiaikoja lukuun ottamatta. Kuitenkin samaan aikaan yksityissijoittajat näkevät ESG rahastot turvallisimpina ja vähemmän volatiileina sijoituskohteina perinteisiin rahastoihin verrattuna. Lisäksi Ei-taloudellisista tekijöistä vahvinta näyttöä saatiin hyvän mielen vaikutuksesta, satunnaisesta syyllisyydestä, sosiaalisista mieltymyksistä ja vahvistusharhasta, joilla havaittiin olevan positiivinen vaikutus yksityissijoittajien sijoituspäätöksiin
Keywords: investors; responsible investing; mutual funds; decision making; behaviour; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|